Personal data protection in the electronic communications sectors - Dobreva, Alena (Yearbook Telecommunications, 2022)
The right to protection of personal data is part of the rights protected under the European Convention on Human Rights, which guarantees the right to respect for private and family life, home and correspondence and defines the conditions under which limitations of this right are allowed. The development of communications and information technology in every public sector makes it increasingly easy to access and process personal data. This requires certain guarantees for the inviolability of personal information and privacy and at the same time implies the existence of clear rules to guarantee this protection. The specificity of data processing in electronic messages requires that, along with the general rules, additional requirements be introduced in the construction of networks and the provision of services.